THE EFFECT OF SHRIMP PROTEIN HYDROLYSATE FORTIFICATION (Acetes erythareus) ON THE QUALITY OF FARFALLE PASTA - Husein, Rheza Aryanda; Suparmi, Suparmi; Sumarto, Sumarto (Politeknik Kelautan dan Perikanan Dumai, 2025)
This study aims to determine the effect of rebon shrimp protein hydrolysate fortification (Acetes erythareus) on the quality of farfalle pasta which includes organoleptic aspects (appearance, texture, aroma, and taste) and chemical content (water content, ash, protein, fat, and carbohydrates). The method used was a non-factorial Completely Randomized Design (CRD) with four fortification concentration treatments, namely 0% (P0), 5% (P5), 10% (P10), and 15% (P15) of the weight of wheat flour. The results showed that the addition of rebon shrimp protein hydrolysate had a significant effect on all quality parameters tested. Treatment P10 was the best treatment based on a combination of organoleptic test results and nutritional content, with characteristics of bright yellow color, typical pasta aroma with a slight shrimp odor, dense and brittle texture, and delicious taste with a touch of shrimp flavor. Proximate values in P10 treatment included water content of 8.79%, ash 1.32%, protein 14.65%, fat 1.39%, and carbohydrate 73.85%. Fortification of rebon shrimp protein hydrolysate was proven to significantly improve the quality and nutritional value of farfalle pasta.